General English as the Foundation of Workplace Communication: Perspectives of Culinary Study Program Students at Akademi Komunitas MAPINDO - Retny Asriyani; I Wayan Agus Anggayana; Ni Putu Lindawati (LPPM Universitas Dhyana Pura, 2026)
English communication competence has become an important requirement for vocational students, particularly in culinary and hospitality fields where interaction with guests, colleagues, and international stakeholders is frequently required. Although previous studies have widely discussed workplace English and English for Specific Purposes (ESP), limited attention has been given to students’ perceptions of the role of General English as a foundation before entering professional communication contexts. This study aims to explore how Culinary Study Program students perceive the contribution of General English instruction to their workplace communication readiness. A qualitative research approach was employed through semi-structured interviews involving 14 students from the Culinary Study Program at Akademi Komunitas MAPINDO. The data were analyzed using thematic analysis following Braun and Clarke’s framework to identify recurring patterns in students’ experiences and perceptions. The findings revealed four main themes: (1) General English as the foundation of language understanding, (2) grammar knowledge supporting communication accuracy, (3) the development of question formation and appropriate responses, and (4) increased confidence in using English during workplace interactions. The students perceived that General English provided essential linguistic knowledge, including grammar, vocabulary, sentence structures, and communication strategies that supported their readiness to communicate during workplace practice. However, students also indicated that foundational English learning should be complemented with workplace-related communication activities to address specific industry demands. This study highlights the importance of maintaining General English as a fundamental component of vocational education, as it provides students with the necessary linguistic and psychological preparation before developing more specialized workplace English skills.